2012
DOI: 10.1029/2012jd017737
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the tropical tropopause layer using the Nonhydrostatic Icosahedral Atmospheric Model (NICAM): 2. An experiment under the atmospheric conditions of December 2006 to January 2007

Abstract: [1] The roles of deep convection and generated waves in the Tropical Tropopause Layer (TTL) are investigated using a global nonhydrostatic model, the Nonhydrostatic Icosahedral Atmospheric Model (NICAM), which runs on the Earth Simulator with a horizontal spacing of 7 km. The model data, which successfully simulated a Madden-Julian Oscillation (MJO) event for the period between 15 December 2006 and 15 January 2007, are analyzed. The frequency of deep convective clouds that reach the TTL is one of the key diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Here we show the results at 16.1 km height. The results at other heights, such as 16.9 km (corresponding to the cold point tropopause in the NICAM simulation, as discussed in section 4 [see Kubokawa et al , , Figure 2]), show similar amplitudes in temperature variations. At all the observatories, low temperatures lasting for about 2 weeks are seen in the second half of almost every month.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Here we show the results at 16.1 km height. The results at other heights, such as 16.9 km (corresponding to the cold point tropopause in the NICAM simulation, as discussed in section 4 [see Kubokawa et al , , Figure 2]), show similar amplitudes in temperature variations. At all the observatories, low temperatures lasting for about 2 weeks are seen in the second half of almost every month.…”
Section: Resultsmentioning
confidence: 99%
“…The vertical spacing of this experiment might appear a little coarse, but it was found that the simulated TTL temperature variation, such as the phase speed associated with Kelvin waves, corresponded closely to the reanalysis data [ Kubokawa et al , ]. The average features, the characteristics of deep convection, and the influence of the waves on the TTL temperature variation were also discussed in Kubokawa et al []. In section 4, we also use the Stretch‐NICAM [ Tomita , ] to investigate the sensitivity of the variability in tropopause temperature to the model configuration.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The dataset was also used to develop a cloud parameterization for coarser resolution AGCMs (Watanabe et al 2009). The convective structure near the tropopause was also analyzed by Kubokawa et al (2012). The energy spectrum and similar frequency spectra of the high-resolution data were analyzed by Terasaki et al (2009) and Tsuchiya et al (2011).…”
Section: Scientific Overview Of Nicammentioning
confidence: 99%